Diseño de un sistema de captación del excedente de vapor, para su aprovechamiento en el calentamiento de agua en la empresa Azulk S.A. (2017)
This project proposes the design of a system for capturing surplus steam, as a solution to an energy and environmental problem starting from the saponification process. The project comprises an initial fieldwork in which information about the processes to be worked is collected, later the thermal and energetic state of said processes and the surplus of steam were determined. The design is established to recover the steam surplus from the 7 saponification reactors and alternative exchangers are proposed to carry out the water heating process for the vacuum feed tank III, after which the most viable alternative is chosen. The design of capture by means of finite elements is evaluated; consecutively, the plans are drawn up.